2022
DOI: 10.1007/s00508-022-02038-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of weekly births and conceptions predicted by meteorology, seasonal variation, and lunar phases

Abstract: Summary Background Data reporting the number of births given by women resident in Vienna for each week between 1999 and 2019, and the duration (in weeks) of their pregnancies, were used to estimate the week of conception. When preliminary examinations detected cyclical patterns for births and conceptions, a series of Poisson regressions for births and conceptions were performed to assess whether these cycles could be associated with lunar or solar phases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The influence of the lunar cycle on births has been widely studied with contrasting results [ 5 – 12 ]. The correlation sought between birth incidence and synodic month (lunar phase, which corresponds to moon illumination percentage) or sidereal month (lunar distance) found by some [ 9 , 11 , 12 ] was not confirmed by others [ 12 ]. We also found no correlation between the synodic or sidereal month and birth.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 94%
“…The influence of the lunar cycle on births has been widely studied with contrasting results [ 5 – 12 ]. The correlation sought between birth incidence and synodic month (lunar phase, which corresponds to moon illumination percentage) or sidereal month (lunar distance) found by some [ 9 , 11 , 12 ] was not confirmed by others [ 12 ]. We also found no correlation between the synodic or sidereal month and birth.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 94%
“…A study conducted in the Netherlands suggested that the time of birth is also affected by the care provider, showing that births of women cared for by midwives peaked earlier in the day compared to women cared for by obstetricians 35 . Timing of birth can also be dependent on weather, season of the year, and lunar phases 36 . However, the hallmark of primate nocturnal deliveries is evident when multiple births, malpresentations, cesarean sections, and vaginal interventions are excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this overview was originally born out of an intention to emulate study results from another study (regarding air pollution and pregnancy loss [2]) with own data. Before the authors analyzed the weekly birth data from Vienna in relation to air quality during pregnancy, they aimed to understand sources of autocorrelation and possibly overdispersion that would -if not controlled for correctlyeventually bias their later results [3]. The use of weekly data in TSA is rare and therefore experience regarding the appropriate way to control for longer-term temporal variations (e.g., seasonal variation) is poor in that case.…”
Section: Methodsmentioning
confidence: 99%
“…Time series analysis (TSA) can be broadly described as the study of time series data, which is characterized by having been sampled or clustered at equally spaced intervals. Common examples include the effect estimates per year [1], sales per month, births or conceptions per week [2,3], suicides per day [4,5], or heart beats per minute. Time series analysis is used in a wide range of fields including physiology [6], economics [7] (e.g., by studying the correlation between economic growth and electricity consumption) [8], ecology (e.g., for predicting the migratory patterns of fish) [9] and genetics (e.g., by exploring biological processes through gene expression) [10].…”
Section: Introductionmentioning
confidence: 99%